Vertebroplasty and kyphoplasty in the management of osteoporotic vertebral compression fractures in elderly individuals: evaluation of the health-related quality of life - Stylianos Kapetanakis; Constantinos Chaniotakis; Periklis Zavridis; Periklis Kopsidas; Sotirios Apostolakis; Nikolaos Gkantsinikoudis (PAGEPress Publications, 2024)
Aim of this study is to investigate the safety, efficacy and impact on Health-Related Quality of Life (HRQoL) of Vertebroplasty (VP) and Kyphoplasty (KP) in the management of Osteoporotic Vertebral Compression Fractures (OVCFs) in elderly individuals. VP and KP represent Minimally Invasive Vertebral Augmentation (MIVA) procedures that are increasingly implemented for surgical treatment of OVCFs in recent years. These interventions have been associated with minimal traumatization and intraoperative hemorrhage, considerable analgesic effect and rapid postoperative recovery. Seventy-seven (77) consecutive individuals with OVCFs were subjected to VP/KP and recruited in this prospectively designed non-randomized study. Clinical evaluation was performed preoperatively and postoperatively at particular chronic intervals at 1, 6 weeks and at 3, 6, 12 months and 2 years. Assessment was conducted via the standardized Visual Analogue Scale (VAS) and Short-Form 36 (SF-36) Medical Health Survey Questionnaire for pain and HRQoL, respectively. No perioperative complications were observed. All studied indices were demonstrated to present a statistically significant amelioration following overall analysis. Pain intensity measured by the VAS score was depicted to be significantly reduced during the first 3 months, but continuous improvement of all indices of SF-36 and VAS was demonstrated to reach a plateau at 6 months, featuring no further clinical improvement.VP and KP represent safe and efficient options for interventional treatment of OVCFs in elderly and oldest-old patients, improving self-reported symptoms of pain as well as overall HRQoL.